Seed Zone Properties and Crop Performance as Affected by Three No-Till Seeders for Permanent Raised Beds in Arid Northwest China - Jin HE; Hong-wen LI; Allen David McHugh; Qing-jie WANG; Hui LI; Rabi Gautam Rasaily; Khokan Kumer Sarker (Journal of Integrative Agriculture, 2012)
The no-till seeders of various soil opener configurations have been shown to produce various soil physical responses in relation to soil and climate conditions, thus affecting crop performance in permanent raised beds (PRB) systems. This is particularly important in arid Northwest China where large volumes of residue are retained on the soil surface after harvest. In Zhangye, Gansu Province, China, a field trial assessed the effects of three typical (powered-chopper, powered-cutter and powered-disc) PRB no-till seeders and one traditional seeder on soil disturbance, residue cover index, bulk density, fuel consumption, plant growth, and subsequent yield. In general, seedbed conditions and crop performance for PRB no-till seeders seeded plots were better than for traditional seeded plots. In PRB cropping system, the powered-chopper seeder decreased mean soil disturbance and increased residue cover index compared to powered-disc and -cutter seeders. However, the results indicated that soil bulk density was 2.3–4.8% higher, soil temperature was 0.2–0.6°C lower, and spring wheat emergence was 3.2–4.7% less. This was attributed to greater levels of residue cover and firmer seedbeds. Spring maize and wheat performance in the powered-cutter and -disc treatments was better (non-significant) than powered-chopper treatment. So powered disc no-till seeder, which generally provided the best planting condition and the highest yield, appeared to be the suitable seeder in heavy residue cover conditions. Considering the precision requirements for soil disturbance and residue cover, the powered strip-chopping no-till seeder could be a suitable option for PRB cropping system in Northwest China. Although these results are preliminary, they are still valuable for the design and selection of no-till seeders for PRB cropping systems in arid Northwest China.